GREEN DINAMIC CAPABILITY IN ENHACING PERFORMA PRODUCT INNOVATION IN THE CREATIVE INDUSTRY SECTOR : THE MODERATING EFFECT OF GREEN CREATIVITY - Ade Suryana; Murtianingsih Murtianingsih; Widi Dewi Ruspitasari (Jurnal Ilmiah Bisnis dan Ekonomi Asia)
This study explores the importance of human resource dynamic capabilities to create product innovation through the mediating role of green creativity in handicraft organizations in Malang-East Java by utilizing natural resources and local wisdom. The purpose of this study is to determine the role of green dynamic capabilities in creating long-term environmentally friendly creativity that will improve the performance of green product innovation. This research method uses a quantitative approach, namely testing the influence of green dynamic capability variables in creating environmentally friendly creativity so that they can create green product innovation performance. The research sample consisted of 96 respondents who met the criteria for creative industry entrepreneurs, then the data analysis stage used PLS-SEM. The results of the study indicate that green dynamic capabilities have a significant effect on environmentally friendly creativity and green product performance, while environmentally friendly creativity also has a significant effect on product performance and is able to mediate the relationship between green dynamic capabilities and product innovation performance.